Does Organic Residue Quality Influence Carbon Retention in a Tropical Sandy Soil?. Issue 3 (19th April 2013) - Puttaso, Aunnop; Vityakon, Patma; Rasche, Frank; Saenjan, Patcharee; Treloges, Vidhaya; Cadisch, Georg
Abstract : The influence of residue quality on soil organic C (SOC) retention has been called into question. A field experiment in Northeast Thailand, in which contrasting quality organic residues were applied yearly for 13 yr, was used to determine quantities, locations, and stability of SOC in the soil matrix and identify residue quality parameters affecting SOC stabilization in a tropical sandy‐textured soil. Total organic C (TOC) content was highest in intermediate‐quality tamarind ( Tamarindus indica L.) at 3.58 g kg −1 (intermediate N, lignin, and polyphenol contents), followed by groundnut ( Arachis hypogaea L.) stover at 2.63 g kg −1 (high N), dipterocarp ( Dipterocarpus tuberculatus Roxb.) at 2.63 g kg −1 (low N, high lignin and polyphenols), and rice ( Oryza sativa L.) straw at 1.77 g kg −1 (high cellulose). Microaggregates (Mi) (0.053–0.25 mm) stored the highest C content (34–49% of TOC), with tamarind having the highest C content. Carbon in large macroaggregates (>2 mm), small macroaggregates (0.25–2 mm), and free organic matter (>0.053 mm) was significantly positively correlated with C, lignin, and polyphenols. Carbon in microaggregates and fine particles (<0.053 mm) was significantly negatively correlated with C/N ratio. Soil fraction C was negatively correlated with residue cellulose contents. Protected C lost through mineralization in Mi was lower in tamarind (7% Mi‐C) followed by groundnut (9.5%), dipterocarp (17.7%), and rice straw (18.6%). It was significantly positively correlated with cellulose and C/N ratios but negatively correlated with N contents. Possible mechanisms of aggregate formation are based on microbial synthesis of both persistent (humic substances) and transient (polysaccharides) binding agents as influenced by residue quality. The results showed clearly that residue quality plays an important role in SOC accumulation in tropical sandy soils.